1992
DOI: 10.1210/endo.131.4.1396327
|View full text |Cite
|
Sign up to set email alerts
|

Glyburide and tolbutamide induce desensitization of insulin release in rat pancreatic islets by different mechanisms.

Abstract: Insulin secretion was studied in rat pancreatic islets after 24-h exposure to various glyburide or tolbutamide concentrations. Glucose-induced insulin release was significantly (P < 0.05) reduced in islets cultured with 0.1 microM glyburide or 100 microM tolbutamide (2098 +/- 187, 832 +/- 93, and 989 +/- 88 pg/islet.h in control, glyburide-exposed, and tolbutamide-exposed islets, respectively). When glyburide-treated islets were stimulated with glyburide or tolbutamide, insulin release was also impaired compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 13 publications
3
15
0
Order By: Relevance
“…It was demonstrated that 1 μmol/L GB acutely promoted basal insulin secretion by approximately 250% in isolated islets, while markedly reduced GSIS in the presence of 16.7 mmol/L glucose. This observation is in good agreement with previous reports [2,23] . The suppressed GSIS might partly result from the reduction of K ATP channel activity induced by chronic exposure to GB and/or the depletion of insulin stores, reflecting the controversy of β-cell desensitization vs β-cell exhaustion [3,24] .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It was demonstrated that 1 μmol/L GB acutely promoted basal insulin secretion by approximately 250% in isolated islets, while markedly reduced GSIS in the presence of 16.7 mmol/L glucose. This observation is in good agreement with previous reports [2,23] . The suppressed GSIS might partly result from the reduction of K ATP channel activity induced by chronic exposure to GB and/or the depletion of insulin stores, reflecting the controversy of β-cell desensitization vs β-cell exhaustion [3,24] .…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, chronic SUs therapy may lead to a selective desensitization of pancreatic β cells to SUs [1,2] . In the present study, the insulinotropic effect of berberine on rat islets was compared with GB, a classical SU derivative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro data confirm that over time, prolonged exposure of insulinsecreting cells to sulphonylureas dramatically decreases their ability to stimulate insulin secretion (Rabuazzo et al 1992, Ball et al 2000a,b, 2004a. These findings highlight the need for a new generation of insulin-releasing drugs.…”
Section: Introductionmentioning
confidence: 82%
“…A study reporting the effect of chronic exposure of sulphonylureas on insulin secretion shows a reversible impairment of insulin release in isolated rat islets after a 24 h pre-exposure to glibenclamide (Gullo et al 1991). Furthermore, desensitization of insulin release in rat islets has been demonstrated to occur secondarily to alterations in ionic fluxes in islets pre-exposed to glibenclamide but not tolbutamide (Rabuazzo et al 1992). The mechanism underlying the -cell hyporesponsivity is not clear.…”
Section: Introductionmentioning
confidence: 99%